Implementation Of Make A Match Type Of Cooperative Methods In Al-Qur'an Hadits Lessons At Junior High School - Anita Rahma (AR-RASYID : Jurnal Pendidikan Agama Islam, 2022)
This study aims to determine the implementation of the Make a Match Type Cooperative Method in Al-Qur'an Hadith Subjects at Ar Rasyid Islamic Middle School, Suka Maju Village, Sunggal District, Deli Serdang Regency. What are the obstacles faced by teachers in its implementation and how to overcome these obstacles. This research is a qualitative research, with the type of field research, and data collection through observation, interviews or interviews, and documentation. The results of the study, namely, the obstacles faced by teachers in implementing the Make a Match Type Cooperative Method in the Subjects of the Qur'an Hadith are that students lack understanding of the make a match type of cooperative learning implementation method and the teacher's lack of creativity in using interesting methods and innovative media. in learning activities. Efforts to overcome the obstacles faced by teachers in its implementation are looking for the right methods and media in learning and varying them.